Engineering of Nebulized Metal–Phenolic Capsules for Controlled Pulmonary Deposition. Issue 6 (10th January 2020) - Ju, Yi; Cortez‐Jugo, Christina; Chen, Jingqu; Wang, Ting‐Yi; Mitchell, Andrew J.; Tsantikos, Evelyn; Bertleff‐Zieschang, Nadja; Lin, Yu‐Wei; Song, Jiaying; Cheng, Yizhe; Mettu, Srinivas; Rahim, Md. Arifur; et al.
Abstract: Particle‐based pulmonary delivery has great potential for delivering inhalable therapeutics for local or systemic applications. The design of particles with enhanced aerodynamic properties can improve lung distribution and deposition, and hence the efficacy of encapsulated inhaled drugs. This study describes the nanoengineering and nebulization of metal–phenolic capsules as pulmonary carriers of small molecule drugs and macromolecular drugs in lung cell lines, a human lung model, and mice. Tuning the aerodynamic diameter by increasing the capsule shell thickness (from ≈100 to 200 nm in increments of ≈50 nm) through repeated film deposition on a sacrificial template allows precise control of capsule deposition in a human lung model, corresponding to a shift from the alveolar region to the bronchi as aerodynamic diameter increases. The capsules are biocompatible and biodegradable, as assessed following intratracheal administration in mice, showing >85% of the capsules in the lung after 20 h, but <4% remaining after 30 days without causing lung inflammation or toxicity. Single‐cell analysis from lung digests using mass cytometry shows association primarily with alveolar macrophages, with >90% of capsules remaining nonassociated with cells. The amenability to nebulization, capacity for loading, tunable aerodynamic properties, high biocompatibility, and biodegradability make these capsules attractive for controlled pulmonary delivery. Abstract : The aerodynamic diameters of metal–phenolic capsules are nanoengineered by increasing their shell thickness, which facilitates tailored capsule deposition in a mechanical lung model. The engineered capsules are promising for pulmonary delivery owing to their robustness for nebulization, biocompatibility, biodegradability, and their capacity for cargo loading and surface functionalization.